Climate change scenarios experiments predict a future reduction in small pelagic fish recruitment in the Humboldt Current system. (3rd April 2013) - Brochier, Timothée; Echevin, Vincent; Tam, Jorge; Chaigneau, Alexis; Goubanova, Katerina; Bertrand, Arnaud
Abstract The Humboldt Current System (HCS) sustains the world′s largest small pelagic fishery. While a cooling of this system has been observed during recent decades, there is debate about the potential impacts of rising atmospheric CO2 concentrations on upwelling dynamics and productivity. Recent studies suggest that under increased atmospheric CO2 scenarios the oceanic stratification may strongly increase and upwelling‐favorable winds may remain nearly constant off Peru and increase off Chile. Here we investigate the impact of such climatic conditions on egg and larval dispersal phases, a key stage of small pelagic fish reproduction. We used larval retention rate in a predefined nursery area to provide a proxy for the recruitment level. Numerical experiments are based on hydrodynamics downscaled to the HCS from global simulations forced by pre‐industrial (PI), 2 × CO2 and 4 × CO2 scenarios. A biogeochemical model is applied to the PI and 4 × CO2 scenarios to define a time‐variable nursery area where larval survival is optimum. We test two distinct values of the oxycline depth that limits larval vertical distribution: One corresponding to the present‐day situation and the other corresponding to a shallower oxycline potentially produced by climate change. It appeared that larval retention over the continental shelf increases with enhanced stratification due to regional warming. However, this increase in retention is largely compensated for by a decrease of the nursery area and the shoaling of the oxycline. The underlying dynamics are explained by a combination of stratification effects and mesoscale activity changes. Our results therefore show that future climate change may significantly reduce fish capacity in the HCS with strong ecological, economic and social consequences.